Co3O4atCN composite material, preparation method thereof and application of Co3O4atCN composite material in visible light catalysis of CO2 cycloaddition
Co3O4@CN composite material was prepared by pyrolysis of UiO-66on ZIF-67 template, which solved the problem of low energy conversion efficiency in the cycloaddition reaction of CO2 and epoxide, and achieved efficient catalytic performance under visible light conditions and Environmentally friendly process improves the utilization efficiency and catalytic performance of light.
Patent Information
- Application Number
- CN202310036669.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-10
- Publication Date
- 2025-01-14
AI Technical Summary
The existing photo-coordinated cycloaddition reaction of CO2 and epoxides has low energy conversion efficiency under full spectrum irradiation conditions, making it difficult to improve the utilization efficiency of light, and traditional heterogeneous catalysts consume a large thermal energy and are not environmentally friendly.
UiO-66on ZIF-67 was used as template pyrolysis to prepare Co3O4@CN composite material, and CO2 and epoxide cycloaddition reaction under visible light conditions, and obtain high metal loading and multi-active sites through direct pyrolysis. Co3O4@CN composite material.
Under visible light irradiation, the utilization efficiency and catalytic performance of light are significantly improved, and the efficient cycloaddition conversion of CO2 and epoxides is achieved, with good practical application value and environmental protection characteristics.
Smart Images

Figure CN119303605A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterial preparation and application, and in particular to a Co3O4@CN composite material and a preparation method thereof and application in visible light-catalyzed CO2 cycloaddition. Background Art
[0002] CO2 is an abundant, cheap, readily available and renewable C1 resource. Catalytic CO2 fixation and conversion has attracted widespread attention from the scientific community. Catalytic conversion of CO2 into high value-added chemicals (such as cyclic carbonates, etc.) is one of the effective ways to alleviate environmental problems. Cyclic carbonates have a wide range of applications in battery electrolytes, clean polar solvents, cosmetic additives, metal extractants, etc. Therefore, the preparation of cyclic carbonates by cycloaddition of CO2 with epoxides has become one of the most valuable reactions in the CO2 directed conversion pathway. Considering its dual benefits in enriching energy supply and reducing CO2 pollution, solar-driven conversion of CO2 into energy-rich chemical fuels has attracted great attention.
[0003] The catalytic systems for catalyzing the conversion of CO2 and epoxides into cyclic carbonates are mainly divided into two categories: homogeneous systems and heterogeneous systems. Homogeneous systems include porphyrins, phthalocyanines, ionic liquids, etc. Because they can be evenly dispersed in the substrate and have a large reaction contact area, they have high catalytic activity and mild reaction conditions. However, highly dispersed homogeneous catalysts are difficult to recover, product separation is difficult, reusability is poor, and practical application value is not high. Heterogeneous systems include metal oxides, molecular sieves, supported catalysts, MOFs, etc. Because the reaction contact area is small and the reaction conditions are harsh, the catalytic activity is relatively low. However, it is easy to separate and recycle, and the synthesized products are easier to purify, which is suitable for industrial large-scale production. Traditional heterogeneous catalysts are mostly thermal catalysts, and the heat energy required for the reaction is converted from electrical energy, which not only consumes a lot of electrical energy, but also may cause secondary emissions of CO2.
[0004] In recent years, the photocatalytic cycloaddition of CO2 and epoxides has been widely studied; photocatalytic CO2 cycloaddition can not only effectively activate stable CO2 molecules and provide sufficient energy sources for the reaction, but also is clean, pollution-free and environmentally friendly. For example, Yang et al. synthesized N-doped carbon materials (Zn SA-NC) loaded with Zn single atoms by direct pyrolysis of N-rich MOF (MET-6); the hierarchical porous structure of Zn SA-NC showed an ultra-high light collection efficiency of >97% in a broadband range (250–2500nm), and also promoted the excitation and transfer of photogenerated electrons to Lewis acid sites (Zn single atom sites), which was beneficial to the adsorption and activation of CO2. It can efficiently catalyze the cycloaddition of CO2 and epoxides under full-spectrum illumination conditions, and the conversion rate and selectivity of epichlorohydrin and CO2 cycloaddition were as high as 99% and 100%, respectively. [Guang-cheng Yang,Lin Gong,Ji Sun,You-song Liu.Photoinduced synergistic catalysis on Zn single-atom-loaded hierarchical porous carbon for highly efficient CO2 cycloadditionconversion.[J].J.Mater.Chem.A,2021,9,2168 9–21694].
[0005] At present, the research on photocatalytic cycloaddition of CO2 and epoxides is mainly carried out under full-spectrum irradiation conditions, which is often affected by low energy conversion efficiency. In order to further improve the efficiency of light utilization, designing and preparing photocatalysts with both visible light response and multifunctional active sites and applying them to efficient photocatalytic CO2 cycloaddition is a difficult problem in current clean energy conversion technology. Summary of the invention
[0006] In order to overcome at least one of the shortcomings and deficiencies of the above-mentioned prior art, the present invention aims to develop a method for preparing a Co3O4@CN composite material by pyrolysis using UiO-66on ZIF-67 as a template and its application in visible light catalytic CO2 cycloaddition. The purpose of the present invention is achieved based on the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a Co3O4@CN composite material, comprising the following steps:
[0008] S1. Preparation of UiO-66 materials;
[0009] S2, adding the obtained UiO-66 material and 2-methylimidazole to anhydrous methanol for ultrasonic mixing, and stirring evenly to obtain a mixed solution; adding Co(NO3)2·6H2O to anhydrous methanol for ultrasonic dissolution to obtain a metal salt solution;
[0010] S3, mixing the obtained metal salt solution and the mixed solution and stirring them evenly, and then standing for a period of time, and then centrifuging and separating the solid product, washing, and drying to obtain UiO-66on ZIF-67 material;
[0011] S4. The obtained UiO-66on ZIF-67 is placed in an air atmosphere for oxidation to obtain a Co3O4@CN composite material.
[0012] Preferably, the preparation of the UiO-66 material in step S1 comprises the following steps:
[0013] S11, adding ZrOCl2·8H2O to N,N-dimethylformamide and dissolving it by ultrasonication to obtain a metal salt solution; adding terephthalic acid to N,N-dimethylformamide and dissolving it by ultrasonication to obtain an organic ligand solution;
[0014] S12, mixing the obtained metal salt solution with the organic ligand solution, adding formic acid after mixing, mixing evenly by ultrasonication, stirring and reacting at 100-130° C. for a period of time, centrifuging and separating the solid product after cooling, washing, and drying to obtain UiO-66 material.
[0015] Preferably, in step S11:
[0016] The molar concentration of ZrOCl2·8H2O in the metal salt solution is 0.5-1.0 mol / L;
[0017] The molar concentration of the organic ligand solution is 0.5 to 1.5 mol / L;
[0018] The organic ligand and the metal salt are dissolved in the solvent by ultrasound, and the ultrasound time is 5 to 30 minutes.
[0019] Preferably, in step S12, the stirring reaction time is 2 to 6 hours.
[0020] Preferably, in step S2:
[0021] The molar concentration of Co(NO3)2·6H2O in the metal salt solution is 0.025-0.50 mol / L;
[0022] The solvent is stirred at a temperature of 10 to 40°C for 30 to 90 minutes;
[0023] The metal salt is dissolved in the solvent by ultrasound, and the ultrasound time is 5 to 30 minutes;
[0024] The drying temperature is 60-110°C and the drying time is 12-36 hours.
[0025] Preferably, in step S2, the mass ratio of UiO-66 material to Co(NO3)2·6H2O is 1:2-15.
[0026] Preferably, in step S3:
[0027] The mixing time is 0.5 to 2 hours, the temperature is 10 to 40°C, and the standing time is 20 to 30 hours;
[0028] The drying is vacuum drying, and the vacuum drying temperature is 60-100°C.
[0029] Preferably, in step S5, the oxidation temperature is 300-500° C., and the oxidation time is 1-4 hours.
[0030] The second aspect of the present invention provides a Co3O4@CN composite material prepared according to the above preparation method.
[0031] The third aspect of the present invention provides an application of a Co3O4@CN composite material in visible light catalytic cycloaddition reaction of CO2 and epoxide at room temperature.
[0032] Preferably, the application method is: mixing the obtained Co3O4@CN composite material with an epichlorohydrin solution, introducing CO2, and performing a cycloaddition reaction under visible light.
[0033] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0034] 1. The preparation method of the present invention is simple and quick to operate, green and environmentally friendly, and low in cost.
[0035] 2. The present invention prepares Co3O4@CN composite material by direct pyrolysis of UiO-66 on ZIF-67, which has ultra-high metal loading and more active sites, can carry out CO2 and epoxide cycloaddition reaction under visible light irradiation conditions, has visible light responsiveness, and high energy conversion efficiency; the Co3O4@CN composite material obtained by the present invention has excellent photothermal conversion performance, can greatly improve the utilization efficiency of light and improve the catalytic performance.
[0036] 3. The Co3O4@CN composite material prepared by the present invention has excellent catalytic performance in the visible light catalytic CO2 and epoxide cycloaddition reaction, strong applicability, and good practical application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1XRD diagram of the Co3O4@CN composite material obtained in Examples 1 to 3;
[0038] Figure 2 This is the SEM image of the Co3O4@CN composite material obtained in Example 3;
[0039] Figure 3 This is a performance diagram of the Co3O4@CN composite material obtained in Example 3 in catalyzing the cycloaddition reaction of CO2 and epoxide under visible light. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] In this example, Co3O4@CN composite material was prepared by direct pyrolysis of UiO-66 on ZIF-67 and applied in visible light catalytic CO2 cycloaddition reaction:
[0043] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0044] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0045] (3) Weigh the UiO-66 material (400 mg) obtained in step (2) and 2-methylimidazole (5.28 g), add them to anhydrous methanol (200 mL), mix them evenly by ultrasonication for 15 min, and stir them at 25 °C for 1 h to obtain a mixed solution C; add Co(NO3)2·6H2O (2.33 g) to anhydrous methanol (200 mL), ultrasonicate for 15 min to dissolve, and obtain a metal salt solution D;
[0046] (4) Mixing the mixed solution C in step (3) with the metal salt solution D, stirring at 25° C. for 1 h, standing for 24 h, centrifuging, washing with anhydrous methanol, and vacuum drying at 80° C. for 12 h to obtain the UiO-66 on ZIF-67 material;
[0047] (5) Weigh the UiO-66on ZIF-67 (100 mg) obtained in step (4), put it into a tube furnace for oxidation in an air atmosphere at 300°C for 2 h, cool it to room temperature and then take it out. The obtained 1#Co3O4@CN material can be used directly.
[0048] (6) Weigh the 1#Co3O4@CN composite material (10 mg) obtained in step (5), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under visible light.
[0049] Example 2
[0050] In this example, Co3O4@CN composite material was prepared by direct pyrolysis of UiO-66 on ZIF-67 and applied in visible light catalytic CO2 cycloaddition reaction:
[0051] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0052] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0053] (3) Weigh the UiO-66 material (400 mg) obtained in step (2) and 2-methylimidazole (5.28 g), add them to anhydrous methanol (200 mL), mix them evenly by ultrasonication for 15 min, and stir them at 25 °C for 1 h to obtain a mixed solution C; add Co(NO3)2·6H2O (2.33 g) to anhydrous methanol (200 mL), ultrasonicate for 15 min to dissolve, and obtain a metal salt solution D;
[0054] (4) Mixing the mixed solution C in step (3) with the metal salt solution D, stirring at 25° C. for 1 h, standing for 24 h, centrifuging, washing with anhydrous methanol, and vacuum drying at 80° C. for 12 h to obtain the UiO-66 on ZIF-67 material;
[0055] (5) Weigh the UiO-66on ZIF-67 (100 mg) obtained in step (4), put it into a tube furnace for oxidation in an air atmosphere at 350°C for 2 h, cool it to room temperature and then take it out. The obtained 2#Co3O4@CN material can be used directly.
[0056] (6) Weigh the 2#Co3O4@CN composite material (10 mg) obtained in step (5), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under visible light.
[0057] Example 3
[0058] In this example, Co3O4@CN composite material was prepared by direct pyrolysis of UiO-66 on ZIF-67 and applied in visible light catalytic CO2 cycloaddition reaction:
[0059] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0060] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0061] (3) Weigh the UiO-66 material (400 mg) obtained in step (2) and 2-methylimidazole (5.28 g), add them to anhydrous methanol (200 mL), mix them evenly by ultrasonication for 15 min, and stir them at 25 °C for 1 h to obtain a mixed solution C; add Co(NO3)2·6H2O (2.33 g) to anhydrous methanol (200 mL), ultrasonicate for 15 min to dissolve, and obtain a metal salt solution D;
[0062] (4) Mixing the mixed solution C in step (3) with the metal salt solution D, stirring at 25° C. for 1 h, standing for 24 h, centrifuging, washing with anhydrous methanol, and vacuum drying at 80° C. for 12 h to obtain the UiO-66 on ZIF-67 material;
[0063] (5) Weigh the UiO-66on ZIF-67 (100 mg) obtained in step (4), put it into a tube furnace for oxidation in an air atmosphere at 400°C for 2 h, cool it to room temperature and then take it out. The obtained 3#Co3O4@CN material can be used directly.
[0064] (6) Weigh the 3#Co3O4@CN composite material (10 mg) obtained in step (5), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under visible light.
[0065] Example 4
[0066] In this example, Co3O4@CN composite material was prepared by direct pyrolysis of UiO-66 on ZIF-67 and applied in visible light catalytic CO2 cycloaddition reaction:
[0067] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0068] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0069] (3) Weigh the UiO-66 material (400 mg) obtained in step (2) and 2-methylimidazole (5.28 g), add them to anhydrous methanol (200 mL), mix them evenly by ultrasonication for 15 min, and stir them at 25 °C for 1 h to obtain a mixed solution C; add Co(NO3)2·6H2O (2.33 g) to anhydrous methanol (200 mL), ultrasonicate for 15 min to dissolve, and obtain a metal salt solution D;
[0070] (4) Mixing the mixed solution C in step (3) with the metal salt solution D, stirring at 25° C. for 1 h, standing for 24 h, centrifuging, washing with anhydrous methanol, and vacuum drying at 80° C. for 12 h to obtain the UiO-66 on ZIF-67 material;
[0071] (5) Weigh the UiO-66on ZIF-67 (100 mg) obtained in step (4), put it into a tube furnace for oxidation in an air atmosphere at 450°C for 2 h, cool it to room temperature and then take it out. The obtained 4#Co3O4@CN material can be used directly.
[0072] (6) Weigh the 4#Co3O4@CN composite material (10 mg) obtained in step (5), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under visible light.
[0073] Example 5
[0074] In this example, Co3O4@CN composite material was prepared by direct pyrolysis of UiO-66 on ZIF-67 and applied in visible light catalytic CO2 cycloaddition reaction:
[0075] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0076] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0077] (3) Weigh the UiO-66 material (400 mg) obtained in step (2) and 2-methylimidazole (5.28 g), add them to anhydrous methanol (200 mL), mix them evenly by ultrasonication for 15 min, and stir them at 25 °C for 1 h to obtain a mixed solution C; add Co(NO3)2·6H2O (2.33 g) to anhydrous methanol (200 mL), ultrasonicate for 15 min to dissolve, and obtain a metal salt solution D;
[0078] (4) Mixing the mixed solution C in step (3) with the metal salt solution D, stirring at 25° C. for 1 h, standing for 24 h, centrifuging, washing with anhydrous methanol, and vacuum drying at 80° C. for 12 h to obtain the UiO-66 on ZIF-67 material;
[0079] (5) Weigh the UiO-66 on ZIF-67 (100 mg) obtained in step (4), put it into a tube furnace for oxidation in an air atmosphere at 500 ° C for 2 h, cool it to room temperature and then take it out. The obtained 5#Co3O4@CN material can be used directly.
[0080] (6) Weigh the 5#Co3O4@CN composite material (10 mg) obtained in step (5), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under visible light.
[0081] Example 6
[0082] In this example, Co3O4@CN composite material was prepared by direct pyrolysis of UiO-66 on ZIF-67 and applied in visible light catalytic CO2 cycloaddition reaction:
[0083] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0084] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0085] (3) Weigh the UiO-66 material (200 mg) obtained in step (2) and 2-methylimidazole (5.28 g), add them to anhydrous methanol (200 mL), mix them by ultrasonication for 15 min, and stir them at 25 °C for 1 h to obtain a mixed solution C; add Co(NO3)2·6H2O (2.33 g) to anhydrous methanol (200 mL), dissolve them by ultrasonication for 15 min, and obtain a metal salt solution D;
[0086] (4) Mixing the mixed solution C in step (3) with the metal salt solution D, stirring at 25° C. for 1 h, standing for 24 h, centrifuging, washing with anhydrous methanol, and vacuum drying at 80° C. for 12 h to obtain the UiO-66 on ZIF-67 material;
[0087] (5) Weigh the UiO-66on ZIF-67 (100 mg) obtained in step (4), put it into a tube furnace for oxidation in an air atmosphere at 400°C for 2 h, cool it to room temperature and then take it out. The obtained 6#Co3O4@CN material can be used directly.
[0088] (6) Weigh the 6#Co3O4@CN composite material (10 mg) obtained in step (5), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under visible light.
[0089] Example 7
[0090] In this example, Co3O4@CN composite material was prepared by direct pyrolysis of UiO-66 on ZIF-67 and applied in visible light catalytic CO2 cycloaddition reaction:
[0091] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0092] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0093] (3) Weigh the UiO-66 material (600 mg) obtained in step (2) and 2-methylimidazole (5.28 g), add them to anhydrous methanol (200 mL), mix them by ultrasonication for 15 min, and stir them at 25 °C for 1 h to obtain a mixed solution C; add Co(NO3)2·6H2O (2.33 g) to anhydrous methanol (200 mL), and dissolve them by ultrasonication for 15 min to obtain a metal salt solution D;
[0094] (4) Mixing the mixed solution C in step (3) with the metal salt solution D, stirring at 25° C. for 1 h, standing for 24 h, centrifuging, washing with anhydrous methanol, and vacuum drying at 80° C. for 12 h to obtain the UiO-66 on ZIF-67 material;
[0095] (5) Weigh the UiO-66on ZIF-67 (100 mg) obtained in step (4), put it into a tube furnace for oxidation in an air atmosphere at 400°C for 2 h, cool it to room temperature and then take it out. The obtained 7#Co3O4@CN material can be used directly.
[0096] (6) Weigh the 7#Co3O4@CN composite material (10 mg) obtained in step (5), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under visible light.
[0097] Example 8
[0098] In this example, Co3O4@CN composite material was prepared by direct pyrolysis of UiO-66 on ZIF-67 and applied in visible light catalytic CO2 cycloaddition reaction:
[0099] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0100] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0101] (3) Weigh the UiO-66 material (800 mg) obtained in step (2) and 2-methylimidazole (5.28 g), add them to anhydrous methanol (200 mL), mix them by ultrasonication for 15 min, and stir them at 25 °C for 1 h to obtain a mixed solution C; add Co(NO3)2·6H2O (2.33 g) to anhydrous methanol (200 mL), dissolve them by ultrasonication for 15 min, and obtain a metal salt solution D;
[0102] (4) Mixing the mixed solution C in step (3) with the metal salt solution D, stirring at 25° C. for 1 h, standing for 24 h, centrifuging, washing with anhydrous methanol, and vacuum drying at 80° C. for 12 h to obtain the UiO-66 on ZIF-67 material;
[0103] (5) Weigh the UiO-66on ZIF-67 (100 mg) obtained in step (4), put it into a tube furnace for oxidation in an air atmosphere at 400°C for 2 h, cool it to room temperature and then take it out. The obtained 8#Co3O4@CN material can be used directly.
[0104] (6) Weigh the 8#Co3O4@CN composite material (10 mg) obtained in step (5), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under visible light.
[0105] The powder diffraction results of the Co3O4@CN composite materials obtained in Examples 1 to 3 are as follows: Figure 1 As shown in Figure 2, all three samples showed the characteristic peaks of the Co3O4 phase, and the characteristic peaks of the Co3O4 phase were weak, indicating that the Co3O4 content in the composite material prepared by the present invention was low or the size was small. The scanning electron microscopy of the Co3O4@CN composite material obtained in Example 3 is as follows Figure 2 As shown in the figure, it is composed of two forms, dodecahedron and octahedron, which indicates that the oxide of UiO-66 on ZIF-67 was successfully synthesized. Example 3 Preparation of Co3O4@CN composite material by direct pyrolysis of UiO-66 on ZIF-67 and application in visible light catalytic CO2 cycloaddition reaction: The performance test results of the material in catalyzing the cycloaddition reaction of CO2 and epoxide under visible light are shown in Figure 3 The results show that the reaction performance of the material obtained by oxidation at a suitable temperature is significantly enhanced, and a conversion rate of 90% and a selectivity of 99% can be achieved within 2 hours, indicating that the Co3O4@CN composite material can greatly improve the utilization efficiency of light and improve the catalytic performance.
[0106] 1. The AAS test (atomic absorption) results of the Co3O4@CN composite materials obtained in Examples 1 to 8 are shown in Table 1:
[0107] Table 1
[0108]
[0109]
[0110] From the results in Table 1, it can be seen that the preferred embodiments of the present invention all obtain Co-containing nanomaterials with ultra-high metal loading and more active sites.
[0111] 2. The performance of the Co3O4@CN composite material obtained in Examples 1 to 8 in catalyzing the cycloaddition of CO2 and epichlorohydrin to generate 1,3-dioxolane-2-one, 4-chloromethyl under visible light was tested. The results are listed in Table 2.
[0112] Table 2
[0113] sample 2h conversion rate 2h Selective <![CDATA[1#Co3O4@CN]]> 69% 99% <![CDATA[2#Co3O4@CN]]> 78% 99% <![CDATA[3#Co3O4@CN]]> 90% 99% <![CDATA[4#Co3O4@CN]]> 85% 99% <![CDATA[5#Co3O4@CN]]> 76% 99% <![CDATA[6#Co3O4@CN]]> 81% 99% <![CDATA[7#Co3O4@CN]]> 74% 99% <![CDATA[8#Co3O4@CN]]> 67% 99%
[0114] The experimental conditions of the catalytic reaction are: catalyst (10 mg), epichlorohydrin (0.1 mmol), tetrabutylammonium bromide (0.1 mmol), N,N-dimethylformamide (2 mL), visible light (400-800 nm), excess CO2, and reaction time of 2 h.
[0115] As can be seen from the data in Table 2, the Co3O4@CN composite material prepared by the present invention has good catalytic activity in the cycloaddition reaction of CO2 and epoxide under visible light, and can reach a conversion rate of ≥67% and a selectivity of 99% within 2 hours, indicating that the Co3O4@CN composite material can improve the photothermal conversion performance, accelerate the mass transfer rate, and improve the catalytic performance; the reaction selectivity is 99%, indicating that there are almost no by-products in the reaction. Among them, the Co3O4 material obtained in Example 3 has the best result in the performance test of the cycloaddition reaction of CO2 and epoxide, and can reach a conversion rate of 90% and a selectivity of 99% within 2 hours, indicating that the reaction performance of the prepared Co3O4@CN material is significantly enhanced.
[0116] Comparative Example 1
[0117] This comparative example provides a method for preparing Co3O4 / CN material, comprising the following steps:
[0118] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0119] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0120] (3) 2-Methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and ultrasonically dissolved for 15 min to obtain an organic ligand solution C; Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and ultrasonically dissolved for 15 min to obtain a metal salt solution D;
[0121] (4) mixing the organic ligand solution C and the metal salt solution D in step (3), stirring for 1 hour, standing for 24 hours, centrifuging, washing with anhydrous methanol, and drying under vacuum at 80° C. for 12 hours to obtain the ZIF-67 material;
[0122] (5) Weigh the UiO-66 material (400 mg) obtained in step (2) and the ZIF-67 material obtained in step (4), respectively, and send them into a tube furnace for oxidation in an air atmosphere at 400° C. for 2 h. After cooling to room temperature, take them out and mix them to obtain the Co3O4 / CN material, which can be used directly;
[0123] (6) Weigh the Co3O4 / CN composite material (10 mg) obtained in step (5), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out cycloaddition reaction under visible light. The Co3O4 / CN material prepared in step (5) catalyzes the cycloaddition reaction of CO2 and epoxide under the same conditions as the Co3O4@CN material prepared in the embodiment of the present invention, with a conversion rate of 51% and a selectivity of 99%.
[0124] Comparative Example 2
[0125] This comparative example provides a method for preparing UiO-66-400 material, comprising the following steps:
[0126] (1) Add ZrOCl2·8H2O (17 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain a metal salt solution A; add terephthalic acid (8.3 g) to N,N-dimethylformamide (100 mL) and dissolve it by ultrasonication for 15 min to obtain an organic ligand solution B;
[0127] (2) The metal salt solution A obtained in step (1) was mixed with the organic ligand solution B, and formic acid (100 mL) was added after mixing, and the mixture was uniformly mixed by ultrasonication for 15 min, and the mixture was stirred at 120° C. for 4 h. After cooling, the mixture was centrifuged, washed with N,N-dimethylformamide and anhydrous methanol, and dried in vacuo at 80° C. for 24 h to obtain UiO-66 material;
[0128] (3) Weigh the UiO-66 material (100 mg) obtained in step (2), put it into a tube furnace for oxidation in an air atmosphere at 400° C. for 2 h, cool it to room temperature and then take it out to obtain the UiO-66-400 material which can be used directly.
[0129] (4) Weigh the UiO-66-400 composite material (10 mg) obtained in step (3), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under visible light.
[0130] The UiO-66-400 material prepared in Comparative Example 2 catalyzes the cycloaddition reaction of CO2 and epoxide under the same conditions as the Co3O4@CN material prepared in Example 3, with a conversion rate of 9% and a selectivity of 99%.
[0131] Comparative Example 3
[0132] This comparative example provides a method for preparing Co3O4 material, comprising the following steps:
[0133] (1) 2-Methylimidazole (5.28 g) was added to anhydrous methanol (200 mL) and ultrasonically dissolved for 15 min to obtain an organic ligand solution A; Co(NO3)2·6H2O (2.33 g) was added to anhydrous methanol (200 mL) and ultrasonically dissolved for 15 min to obtain a metal salt solution B;
[0134] (2) mixing the organic ligand solution A and the metal salt solution B in step (1), stirring for 1 hour, and then standing for 24 hours, and then centrifuging, washing with anhydrous methanol, and vacuum drying at 80° C. for 12 hours to obtain the ZIF-67 material;
[0135] (3) Weigh the ZIF-67 material (100 mg) obtained in step (2), place it into a tube furnace for oxidation in an air atmosphere at 400° C. for 2 h, cool it to room temperature and then take it out to obtain the Co3O4 material that can be used directly.
[0136] (4) Weigh the Co3O4 composite material (10 mg) obtained in step (3), epichlorohydrin (0.1 mmol), and tetrabutylammonium bromide (0.1 mmol), and dissolve them in N,N-dimethylformamide (2 mL); introduce CO2 and carry out a cycloaddition reaction under visible light.
[0137] The Co3O4 material prepared in Comparative Example 3 catalyzes the cycloaddition reaction of CO2 and epoxide under the same conditions as the Co3O4@CN material prepared in Example 3, with a conversion rate of 42% and a selectivity of 99%.
[0138] By comparing the catalytic performance results of Comparative Examples 1 to 3 with those of Example 3, it was found that the Co3O4@CN composite material obtained by direct pyrolysis of UiO-66onZIF-67 in Example 3 had excellent performance in catalyzing the cycloaddition reaction of CO2 and epoxide under visible light, and had good practical application value.
[0139] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a Co3O4@CN composite material, characterized in that: The following steps are involved: S1. Preparation of UiO-66 materials; S2, adding the obtained UiO-66 material and 2-methylimidazole to anhydrous methanol for ultrasonic mixing, and stirring evenly to obtain a mixed solution; adding Co(NO3)2·6H2O to anhydrous methanol for ultrasonic dissolution to obtain a metal salt solution; S3, mixing the obtained metal salt solution and the mixed solution and stirring them evenly, and then standing for a period of time, and then centrifuging and separating the solid product, washing, and drying to obtain UiO-66on ZIF-67 material; S4. The obtained UiO-66on ZIF-67 is placed in an air atmosphere for oxidation to obtain a Co3O4@CN composite material.
2. The method for preparing a Co3O4@CN composite material according to claim 1, characterized in that: The preparation of the UiO-66 material in step S1 comprises the following steps: S11, adding ZrOCl2·8H2O to N,N-dimethylformamide and dissolving it by ultrasonication to obtain a metal salt solution; adding terephthalic acid to N,N-dimethylformamide and dissolving it by ultrasonication to obtain an organic ligand solution; S12, mixing the obtained metal salt solution with the organic ligand solution, adding formic acid after mixing, mixing evenly by ultrasonication, stirring and reacting at 100-130° C. for a period of time, centrifuging and separating the solid product after cooling, washing, and drying to obtain UiO-66 material.
3. The method for preparing a Co3O4@CN composite material according to claim 2, characterized in that: In the step S11: The molar concentration of ZrOCl2·8H2O in the metal salt solution is 0.5-1.0 mol / L; The molar concentration of the organic ligand solution is 0.5 to 1.5 mol / L; The organic ligand and the metal salt are dissolved in the solvent by ultrasound, and the ultrasound time is 5 to 30 minutes.
4. The method for preparing a Co3O4@CN composite material according to claim 2, characterized in that: In the step S12: the stirring reaction time is 2 to 6 hours.
5. The method for preparing a Co3O4@CN composite material according to claim 1, characterized in that: In step S2: The molar concentration of Co(NO3)2·6H2O in the metal salt solution is 0.025-0.50 mol / L; The solvent is stirred at a temperature of 10 to 40°C for 30 to 90 minutes; The metal salt is dissolved in the solvent by ultrasound, and the ultrasound time is 5 to 30 minutes; The drying temperature is 60-110°C and the drying time is 12-36 hours.
6. The method for preparing a Co3O4@CN composite material according to claim 1, characterized in that: In the step S2, the mass ratio of UiO-66 material to Co(NO3)2·6H2O is 1:2-15.
7. The method for preparing a Co3O4@CN composite material according to claim 1, characterized in that: In step S3: The mixing time is 0.5 to 2 hours, the temperature is 10 to 40°C, and the standing time is 20 to 30 hours; The drying is vacuum drying, and the vacuum drying temperature is 60-100°C.
8. The method for preparing a Co3O4@CN composite material according to claim 1, characterized in that: In step S5, the oxidation temperature is 300-500° C., and the oxidation time is 1-4 hours.
9. A Co3O4@CN composite material, characterized in that: Prepared according to the preparation method described in any one of claims 1 to 8.
10. Use of the Co3O4@CN composite material according to claim 9 in visible light photocatalytic cycloaddition reaction of CO2 and epoxide at room temperature.
Citation Information
Patent Citations
Preparation method of electrocatalytic full-decomposition water material based on ZIF-67 and UiO-66 double MOFs
CN111871463A
Hydroxide-coated ZIF series MOFs heterogeneous catalyst and preparation method and application thereof
CN112371189A
Metalloporphyrin-based porous polymer, preparation thereof and application of metalloporphyrin-based porous polymer in catalysis of cycloaddition reaction of carbon dioxide and epoxide
CN113185701A
Preparation method and application of magnetic Co@CN nano material
CN113457709A
Preparation method of porous nitrogen-doped carbon material supported cobalt-based catalyst and application of porous nitrogen-doped carbon material supported cobalt-based catalyst in reaction for preparing high-carbon alcohol through CO hydrogenation
CN114522708A